PNI Political Strategy to Win the 1955 Election in Indonesia - Agustina Wilujeng Pramestuti; Yety Rochwulaningsih; Singgih Tri Sulistiyono (IHiS (Indonesian Historical Studies), 2022)
This article aims to reveal the reason and how the Indonesian Nationalist Party (PNI) succeeded in becoming the winning party of the General Election (Pemilu) in Indonesia in 1955 by gaining the most votes as many as 8,434,653 votes, followed by the Indonesian Muslim Shura Council Party (Masyumi) of 7,903,886 votes and Nahdlatul Ulama Party (NU) of 6,955,141 votes. The 1955 election was the first direct election in Indonesia to be the most democratic in history since the campaign did not only take place in big cities, but had reached villages and even remote villages. The atmosphere of contestation was very strong, but it was not accompanied by a violent conflict even though the contestation was from political parties with very different ideological backgrounds. In this context, the political strategy pursued by the PNI is very interesting, that is by consolidating politics both internally and externally. To examine the problems, historical methods were used in which data were excavated from primary sources including news and articles in newspapers and magazines, as well as minutes of parliamentary meetings regarding the Election. The results of the analysis showed that the PNI performed politics consolidation through cooperation with various groups and political parties of any ideology. In addition, the PNI also adopted the conception of Sukarno's thinking to mobilize supporters, including through meetings, open meetings attended by the people by presenting prominent nationalist figures as their orators. The issues raised in the campaign had distinctive characteristics of nationalism, citizenship, and mutual cooperation.